A new beta-diketone complex with high color purity - Adati, R. D.; Lima, S. A. M.; Davolos, Marian Rosaly [UNESP]; Jafelicci, M. (Elsevier B.V., 2006)
In this work a new europium (III) complex with the following formula NH(4) [Eu(bmdm)(4)] was synthesized and characterized. The bmdm (butyl methoxy-dibenzoyl-methane) is a P-diketone molecule used as UV radiation absorber in sunscreen formulations. Coordination of this ligand to the Eu(3+) ion was confinned by FT-IR, while the Raman spectrum suggests the presence of NH(4)(+) ions. The photoluminescence spectra present narrow lines arising from f-f intra-configurational transitions (5)D(0-)(7)F(0,1,2,3,4), dominated by the hypersensitive (5)D(0)-(7)F(2) transition. In the spectrum recorded at 77 K, all transitions split into 2J + 1 lines suggesting that there is just one symmetry site around Eu(3+) ion. This symmetry is not centrosymmetric. The calculated intensity parameters are ohm(2) = 30.5 x 10(-20) cm(2) and ohm(4) = 5.91 x 10(-20) cm(2) for this complex. The CIE chromaticity coordinates (x = 0.67 and y = 0.32) show a dominant wavelength of 615 nm. The color gamut achieved by this complex is a 100% in the CIE color space. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: phosphor; chemical synthesis; electronic states; light absorption; luminescence